Ayurvedic Management of Female Infertility Associated with PCOD and Tubal Obstruction (AYUSHDHARA, 2025)
Experience of infertility can place significant emotional and psychological burdens on those going through it. It generally refers to the inability to conceive after a year of regular, unprotected intercourse, or the inability to carry a pregnancy to term. According to the World Health Organization (WHO), approximately 17.5% of the adult population worldwide equivalent to one in six individuals experience infertility during their lifetime and there are various reasons behind the infertility. In Ayurveda an umbrella term Vandhyatwa is used to denote any kind of infertility and four factors such as Ritu, Ambu, Kshetra, Beeja are responsible for the reproduction. Any defect on the single factor hinders the fertility. In this case study a 26 year old female, married for three years, presented with infertility attributed to PCOD with left para ovarian cyst (Beeja dusti) and bilateral tubal obstruction (Kshertaj dusti), provide with Shodana and Shaman Chikitsa including Anuvasana Basti with Dashmool Taila and Asthapana with Dashmool kwatha in the form of Yoga Basti and Uttar Basti with Ksheerbala taila. Following two months of this Ayurvedic treatment regimen, the patient successfully conceived, demonstrating a significant improvement in reproductive health. This case underscores the potential of Ayurvedic treatments, particularly through the application of Sodhana and Shamana Chikitsa, in managing infertility related to PCOD and tubal obstruction.